Genetic characterization of natural populations of pineapple guava (Acca sellowiana), with heterologous microsatellites markers - Karine Louise dos Santos (Biotemas, 2011)
Pineapple guava (Acca sellowiana) is a native species from south Brazil and northeast Uruguay, and due to the unique flavor of its fruits, it is an income-generating alternative to small farmers. Knowledge on genetic diversity is an important tool for genetic improvement and conservation. Aiming to increase the knowledge with regarde to the species genetic diversity, fi ve natural populations of A. sellowiana were analyzed through microsatellites markers developed from Eucalyptus grandis W. Hill ex Maiden x E. urophylla S.T. Blake complex. Using 10 pairs of selected markers, 122 plants were characterized. The mean values for expected and observed heterozigosity were 0.42 and 0.47, respectively. The fˆ estimates did not differ from zero to four out of the five populations evaluated, suggesting a small inbreeding effect. In addition, private alleles and high genetic divergence was observed. the average genetic divergence among the populations was st Fˆ = 0,13 e st Rˆ = 0,14, mostly due to the incidenceof rare or exclusive alleles among some populations.